Community-embedded learning experiences: putting the pedagogy of service-learning to work in online courses. (2nd January 2017) - Becnel, Kim; Moeller, Robin A.
Abstract: This paper considers the applicability and adaptability of service-learning pedagogy to online and distance education teaching environments. More specifically, it looks at the community-embedded learning model (CEL), which asks distance students to conduct service projects in their local communities, as manifested in a project undertaken by online graduate students in the library science programme at Appalachian State University, a mid-sized university in the United States of America. For this assignment, students, who are located throughout the state of North Carolina and surrounding areas, performed service work in libraries located within their own communities and neighbourhoods, coming together to discuss their experiences in regular synchronous course meetings conducted online. In addition to describing this project, this paper will offer analysis of student reflections, describing what students perceived as challenging, important and rewarding about the experience. Through this study, the researchers highlight the potential value of community-embedded learning experiences for classes conducted in online environments.